IP-enabled energy management a proven strategy for administering energy as a service - Aldrich, Robert, 1973-; Parello, John, 1966-; ebrary, Inc. (Hoboken, N.J. : Wiley Technology Pub., 2010)
"Based on a real energy management program that author Rob Aldrich implements at Cisco, this book shows you how to implement an energy management strategy that has proven to reduce and control energy costs by establishing energy as a domain that network administrators help manage for their company. In this book, you will find step-by-step instruction for implementing a comprehensive energy management strategy, beginning with benchmarking and eventually coming full circle with re-investing savings back into the program for its sustainability. The book also covers fundamentals of efficiency energy use, project management, deployment and administration of energy domains, and reporting. Hands-on instruction is emphasized in this book and case studies of the author's implementation at Cisco appear throughout the book and collectively as a complete case study."--
Includes index.
Electronic reproduction.
Keywords: Cisco Systems, Inc. -- Automation; Energy conservation; Energy consumption -- Automatic control; Computer networks; Electronic books